2012
DOI: 10.1021/ja3031467
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of anti- and syn-Homopropargyl Alcohols via Chiral Brønsted Acid Catalyzed Asymmetric Allenylboration Reactions

Abstract: Chiral Brønsted acid catalyzed asymmetric allenylboration reactions are described. Under optimized conditions, anti-homopropargyl alcohols 2 are obtained in high yields with excellent diastereo- and enantioselectivities from stereochemically matched aldehyde allenylboration reactions with (M)-1 catalyzed by the chiral phosphoric acid (S)-4. The syn-isomers 3 can also be obtained in good diastereoselectivities and excellent enantioselectivities from the mismatched allenylboration reactions of aromatic aldehydes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 109 publications
0
32
0
Order By: Relevance
“…The preparation of the required northern fragment started from propargyl alcohol, which was hydrosilylated to give product 33 on scale (Scheme ). The derived aldehyde 34 was reacted with allenylboronate 35 in the presence of ( R )‐TRIP (5 mol %) to afford the anti ‐configured homopropargyl alcohol 36 in high yield and selectivity . After formation of phosphonoacetate ester 40 (Scheme ), a Still–Gennari olefination with aldehyde 32 furnished Z ‐ 41 in 67 % yield along with the corresponding E ‐isomer ( Z / E= 6:1), which were separable by standard flash chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of the required northern fragment started from propargyl alcohol, which was hydrosilylated to give product 33 on scale (Scheme ). The derived aldehyde 34 was reacted with allenylboronate 35 in the presence of ( R )‐TRIP (5 mol %) to afford the anti ‐configured homopropargyl alcohol 36 in high yield and selectivity . After formation of phosphonoacetate ester 40 (Scheme ), a Still–Gennari olefination with aldehyde 32 furnished Z ‐ 41 in 67 % yield along with the corresponding E ‐isomer ( Z / E= 6:1), which were separable by standard flash chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The deriveda ldehyde 34 was reacted with allenylboronate 35 in the presence of (R)-TRIP (5 mol %) to afford the anti-configured homopropargyl alcohol 36 in high yield and selectivity. [46] After formation of phosphonoacetate ester 40 (Scheme 8), aS till-Gennari olefination with aldehyde 32 furnished Z-41 in 67 %y ield alongw ith the corresponding E-isomer (Z/E = 6:1), which were separable by standard flash chromatography.T he subsequentm acrocyclization by RCAM proceeded once again smoothly with the help of the molybdenum alkylidyne 20,w hicha ttests to the excellent selectivity of the catalystf or alkynes in the presence of other psystems.…”
Section: Afirst Approach Towards Callyspongiolidementioning
confidence: 99%
“…Moreover, during the search for the best reaction conditions, the authors observed that better results (2–12 times better) were obtained using PCy 3 in the presence of CuCl and KO t Bu during the reactions (62–97 %) rather than Pd(PPh 3 ) 4 catalyst with CuI (5–70 %). The research work of Szabo and co‐workers contributed to the broader application of allenyl and propargyl boronates as key reagents in the synthesis of conjugated compounds as well as natural products …”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
“…[32] Previous studies had shown that the axial chirality of 3-substituted allenylboron species such as (M)-113 is transferred to ther esulting homopropargyl alcohol ent-115 upon reactionw ith an aldehyde and that chiral phosphoric acid 23 can influence the preferred transition state leadingt od iastereoselectivity. [33] Here, the authors utilized the corresponding finding that there is am atched/mismatched pairing between each enantiomer of the allene and the catalyst that influences the rate of reaction. In this kinetic resolution the matched allene reacts faster in the proposed TS-1 to give anti product 115 while the unmatched allene reacts more slowly to give the syn product 116.B yu sing an excesso f allenylboronate (AE)-113,g ood yields and enantiopurity of the anti-homopropargyl alcohol 115 were obtained.…”
Section: Miscellaneous Brønsted Acid Catalyzed Kinetic Resolutionsmentioning
confidence: 99%